Hubungan Konsep Diri dengan Kesiapan Menikah - Azahra Hardi Cusinia; Taufik Taufik (Universitas Negeri Padang, 2023)
The background of this research is that many young married couples experience divorce due to a lack of readiness to marry. This lack of readiness creates conflict between husband and wife due to poor self-concept. This study aims to describe: (1) the self-concept of Faculty of Education Universitas Negeri Padang (FIP UNP) students in the class of 2019. (2) readiness to marry FIP UNP students in the class of 2019. (3) Find a correlation between self-concept and readiness to marry FIP UNP students in the class of 2019. This research uses a quantitative approach with a correlational research type. The research subjects were 91 non-counseling FIP UNP students. The instrument used was a scaled questionnaire, which was analyzed using a percentage scale technique. The correlation between the two variables was analyzed using the Pearson Product Moment Correlation technique. The results showed that (1) students' self-concept was in the high category with an average achievement score of 72%; (2) students' readiness to marry was in the very high category with an average achievement score of 74%; and (3) there was a positive relationship with a significant difference between self-concept and students' readiness to marry with a correlation of 0.756 using a significant level of 0.01. So, if the student's self-concept is positive, then the student's readiness to marry will also have a positive impact, and vice versa, if the student's self-concept is negative, it will also reduce the student's readiness to marry.